Using 3–D method of boundary elements for calculation of stresses and displacement distribution for engineering objects of complex structure. (4th August 2014) - Kupreev, N.; Shternshis, A.
The development of computer–aided design (CAD) over the past twenty years has passed through many stages. The most recent stage has been the need to create methamodels as a new modelling framework for the design of objects. The development of algorithms for numerical research of stresses and displacement distribution in 3–D modelling of different objects constitutes an important component in the creation of methamodels. An algorithm for the numerical solution of the problem of the theory of elasticity for complex objects is presented here.